Interactions in the multilingual classroom : a case study of teacher beliefs and student attitudes on L1 use in multilingual classrooms : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Second Language Teaching at Massey University, Palmerston North, New Zealand - Tan, Siaw Ping (Massey University, 2015)
The subject of L1 use in target language classrooms has been the object of debate among practitioners of second and foreign language teaching. As second language learners are de facto speakers of another language, student use of L1 remains a core feature of second language (L2) or target language (TL) classrooms, making the L1 almost impossible to eliminate. Despite increasing literature supporting the L1 as playing instrumental cognitive and affective roles that enhance L2 or TL learning, the English-only approach has been preferred and prescribed by both official and non-official policies in English Language Teaching. This thesis explores English language teacher beliefs and student attitudes about L1 use in multilingual classrooms in a New Zealand university language centre. A mixed method approach has been employed in order to obtain a more holistic view of the participants’ beliefs and attitudes. Results indicate that despite an English-only rule, both teachers and students view L1 use in the classroom setting as a potentially beneficial language learning tool - especially at lower levels. However, teachers and students generally perceived English as the preferred in-class instruction language due to the students studying in a New Zealand university environment. Tensions emerged when the teachers perceived an over-reliance on student L1 use in the classroom most especially due to lack of English language proficiency and/or lack of interest to participate in classroom activities in English. The thesis concludes with recommendations on how the monolingual rule can be modified to reflect the multilingual classroom environment and how students could be made more aware of classroom expectations in a New Zealand university prior to arrival.
Keywords: Second language learning; Second language teaching; English as a second language; Multilingual classrooms; Native language use in education; English language teachers; English language students